MARKETING AUDIT AND ITS IMPACT ON IMPROVING THE COMPETITIVENESS OF THE COMPANY - Nabieva , Nilufar (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
Currently, the processes of globalization of the world economy have turned the priorities of companies, and require them to systematically analyze favorable and crisis situations in marketing, as well as promptly respond to them. To ensure the necessary level of competitiveness, companies are looking for new and more advanced methods of analyzing their marketing activities that will allow them to adjust their policies and choose ways to increase competitiveness. As a result, a marketing audit was developed. The article analyzes the impact of marketing audit on the competitiveness of the company.